Innovations in travel demand modeling. Volume 2, summary of a conference [held] May 21-23, 2006, Austin Texas - Turnbull, Katherine F. (Conference proceedings (National Research Council (U.S.). Transportation Research Board) ;, 2008)
"TRB Conference Proceedings 42, Innovations in Travel Demand Modeling, Volume 2: Papers includes the papers that were presented at a May 21-23, 2006, conference that examined advances in travel demand modeling, explored the opportunities and the challenges associated with the implementation of advanced travel models, and reviewed the skills and training necessary to apply new modeling techniques. TRB Conference Proceedings 42, Innovations in Travel Demand Modeling"--Publisher's description